Uniformità della giurisprudenza e unitarietà della scienza: la misura di sostenibilità del pluralismo (TEST BioLaw Journal - Rivista di BioDiritto, 2016)
The need of translating health requests – deeply affected by individual moral conceptions of life, wellbeing and illness – into protected rights, represents today a tough challenge for judges to be solved. The judiciary is, in fact, often called to play a fundamental role in selecting individual positions to be granted protection. The inescapable relation between the two dimensions of the right to health – the individual and the collective one – requires a constant activity of balancing different positions. On this premise, the paper focuses on two different fields in which individual health-related demands put judges in front of a pluralistic scenario in need to be filtered through constitutional principles. The first is related to vaccines policies, both in the USA and in Italy and to the consequences deriving from the growth of the anti-vaccine movement. The second example comes from the deceptive stem cells therapies offered in Italy by Stamina Foundation. In answering some of these cases, judges found themselves pressed by dramatic individual needs and eventually come to forget science, its methods and its procedures. The paper aims at identifying contradictions and inconsistencies of the described jurisprudence in order to realign law and science, to re-establish roles and methods of both disciplines and to mark the borders of a sustainable form of pluralism.
Keywords: Pluralisms; Moral values; Right to health; Vaccines; Stem cells therapies